The changing landscape of food deserts - KARPYN, ALLISON E. (UNSCN Nutr, 2019)
In this article, we discuss the most recent trends in food-retail access in low- and moderate-income communities in the United States of America. We begin with a review of the current literature on the number of people impacted by food deserts and then review several critical retail trends, including supercentres (such as Walmart),() dollar stores, farmers markets and online food retail. We discuss the growing investment in incentive programmes, as well as new understandings of the impact of food deserts on health. In the United States of America, the number of communities without adequate access to healthy affordable food has declined, though more than 5.6 percent of the population still lives in low-access census tracts. At the same time, racial and economic disparities in food access remain a considerable concern, with around 30 percent more non-white residents facing limited access to food retail than white residents. We also provide recommendations for areas of future research.